Pivot Polytopes of Products of Simplices and Shuffles of Associahedra - Pilaud, Vincent; Poullot, Germain (Discrete & computational geometry, 2025)
We provide a piecewise linear isomorphism from the normal fan of the pivot polytope of a product of simplices to the normal fan of a shuffle of associahedra.